The complete project manager's toolkit - Englund, Randall L; Bucero, Alfonso, 1956- (Tysons Corner, VA : Management Concepts Press, 2012)
This companion to The complete project manager provides the tools you need to integrate key people, organizational, and technical skills.
Includes bibliographical references (p. [201]-203).
oif 12/06/15
Loan
Keywords: Project managers -- Training of -- Handbooks, manuals, etc; Project management -- Handbooks, manuals, etc; Project Integration Management (Knowledge Area)